The Strange, Second Death of Lewis Yealland - Duffy, Dennis (Ontario History)

(untitled) (The Ontario Historical Society, 2011)
Lewis Ralph Yealland (1885-1954), a graduate of University of Western Ontario’s medical school, migrated to the imperial capital in 1915, where he worked on shell-shock cases at the Queen’s Square hospital. His efforts won him the praise of his superiors, and he published a survey of his cases and the therapies he employed in 1918. He spent the remainder of his career as a Harley Street physician, specializing in the treatment of alcoholism. UWO granted him an honourary degree in 1948. Then, beginning in 1985, his reputation began its posthumous disintegration. Scholars, a prominent novelist, and a filmmaker alike viewed him and his electroshock therapies as barbarous. Yet a carefully contextualized account of his practices compels us to revise this recent revisionism. Neither an attempt at advocacy nor a venture in setting the record straight, my treatment of Yealland and his work on shell-shock provides an alternative reading to a subject that contemporary discourse made up it mind about too quickly.